The Religious View of Azerbaijan Intellectuals (1885-1915) - Sovgatov, İlham (CenRaPS Journal of Social Sciences, 2022)
In this study, the views of Azerbaijani intellectuals about religion are discussed. XIX. XX with the last quarter of the century. The views of some of the Azerbaijani intellectuals who lived and produced ideas in the years covering the first quarter of the century are mentioned. This period covers the last years of Tsarist Russia of Azerbaijan and the People's Republic of Azerbaijan. The issues discussed by Azerbaijani intellectuals in this period can be listed as follows: Progress, nationalism, Turkism, statism, libertarianism, unionism, Islamism, contemporaryism and Europeanization (Westernization). Almost all of these concepts are concepts that have entered into circulation in Western thought in the modern period and have been adopted and discussed by Azerbaijani intellectuals. In this context, it is possible to say that Azerbaijani intellectuals have accepted the military, economic, political and scientific superiority of the West, and that they have adopted the opinion that development can be possible by taking a Western-style management system as an example in the social structure. In this study, the views of Mirze Celil Memmedguluzade, poet Mirze Elekber Sabir, musician and composer Üzeyir Hacıbeyli, who were among the thinkers who took an active role in both literature and politics, were included in this study. At the same time, the critical views of the "Molla Nasreddin" magazine, which saw the light of day in the said period, against religion are also discussed.